2017
DOI: 10.4172/2155-9600.1000642
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Nutrient Intake in Patients with Inflammatory Bowel Disease

Abstract: Patients with inflammatory bowel diseases (IBD) are often affected by nutrient deficiencies. Besides a limited nutrient intake by disease-related side effects and malabsorption, the influence of diets and dietary changes is much discussed. However, data about food patterns are mostly based on subjective declarations. Therefore, this study aimed to achieve a detailed and objective analysis of nutrient intake and individual food habits in IBD, a prerequisite for an appropriate nutritional intervention in risk pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…In agreement to a study by Schink et al (10) , we found that the overall nutrient intake was higher in carbohydrates and lower in fat. Also Zopf et al (11) revealed that all IBD patients had considerably consumed larger absolute amounts of carbs, which is consistent with the findings of an earlier investigation.…”
Section: Resultssupporting
confidence: 94%
“…In agreement to a study by Schink et al (10) , we found that the overall nutrient intake was higher in carbohydrates and lower in fat. Also Zopf et al (11) revealed that all IBD patients had considerably consumed larger absolute amounts of carbs, which is consistent with the findings of an earlier investigation.…”
Section: Resultssupporting
confidence: 94%
“…While some of these solutions are already in use in biomedical research projects [e.g. (61)], a major issue remains: the dietary information obtained cannot be treated as objective and thereby does not meet the criteria for a source of potential medical biomarkers (62).…”
Section: Challenges and Potential Solutions Precision In Dietary Assementioning
confidence: 99%